1990
DOI: 10.1159/000235123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Toxocara canis </i>Infection on Hemopoietic Stem Cells and Hemopoietic Factors in Mice

Abstract: The effects of Toxocara canis infection on hemopoietic stem cells and hemopoietic factors were examined in mice. Severe eosinophilia was observed with a peak 14 days after infection. When the numbers of hemopoietic stem cells in peripheral blood, spleen, and bone marrow were examined by spleen colony assay (CFU-S), those in peripheral blood and spleen increased in parallel with peripheral blood eosinophilia. On the other hand, CFU-S in bone marrow did not alter significantly throughout the course of infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1992
1992
1996
1996

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Because no EDA was detected in media conditioned by lungs and spleen cells of non-infected nu/nu and nu/+ mice, IL-5 production by lung cells of both mice and spleen cells of nu/+ mice was an effect related to infection. Although IL-5 production by spleen cells of T. canis infected mice were reported previously (Higa et al 1990, Yamaguchi et al 1990), we reported here for the first time that lung cells of infected nu/nu and nu/+ mice produced IL-5 when stimulated by antigen. These results indicate the mechanism of eosinophilia in T. canis infected nujnu mice.…”
Section: Discussioncontrasting
confidence: 49%
“…Because no EDA was detected in media conditioned by lungs and spleen cells of non-infected nu/nu and nu/+ mice, IL-5 production by lung cells of both mice and spleen cells of nu/+ mice was an effect related to infection. Although IL-5 production by spleen cells of T. canis infected mice were reported previously (Higa et al 1990, Yamaguchi et al 1990), we reported here for the first time that lung cells of infected nu/nu and nu/+ mice produced IL-5 when stimulated by antigen. These results indicate the mechanism of eosinophilia in T. canis infected nujnu mice.…”
Section: Discussioncontrasting
confidence: 49%